Strategi Penyelarasan Kurikulum Pembelajaran dengan Dunia Industri di Konsentrasi Teknik Instalasi Tenaga Listrik SMK Negeri 2 Pandeglang Tahun Ajaran 2023/2024 - Fina Ayu Lestari; Ragil Febrian; Muamar Ilham Zaini; Rifqi Badruzzaman; Afandhi Afandhi (Simpati, 2023)
This research focuses on school strategies in aligning the learning curriculum with the industrial world in the Electrical Power Installation Engineering Concentration at SMK Negeri 2 Pandeglang for the 2023/2024 Academic Year. The curriculum used at SMK Negeri 2 Pandeglang is based on independent learning. The research method used is a qualitative research method, which involves collecting data by observation, interviews and documentation. The research results were obtained based on observations and interviews with the Deputy Principal for Curriculum and the Head of the Electrical Power Installation Engineering Concentration Program.